Search for $Z'→τ_μ τ_h$ in full LHC-run II data with the CMS detector (2024)
Beyond standard model (BSM) theories have proposed additional neutral boson particles that could provide insights into the Standard Model's issues \cite{bsm}. For instance, searches have been performed for a neutral gauge boson called $Z'$, a particle with similar properties to the neutral $Z$ massive boson from the SM. There are many ways to generate additional neutral gauge bosons, like extending the SM symmetries or from other frameworks like Grand Unified Theories (GUT), string theories, and extensions of the SM. Finding a $Z'$ boson would have exciting implications because requiring additional gauge $U(1)'$ symmetries would generate an extended Higgs sector and, in the case of supersymmetric models, extended neutralino sectors \cite{zprime}. $Z'$ boson searches are well motivated by those BSM scenarios that predict these particles with masses at the TeV order \cite{cdf,dzero} since these would be produced at the current energies of the Large Hadron Collider (LHC) at CERN \cite{atlas,cms}. In the current $Z'$ boson searches, there is an interest in models that include extra neutral gauge bosons that decay into pairs of high-transverse momentum tau leptons, like for example the sequential standard model (SSM) \cite{ssm}, which predicts a neutral spin-1 boson, denoted $Z'_{SSM}$. Since the tau lepton has different decay modes, the search for $Z'$ bosons involves four possible final state experimental signatures: $τ_hτ_h$, $τ_hτ_e$, $τ_hτ_μ$ and $τ_eτ_μ$ where $τ_h$ is a tau lepton that decays hadronically and $τ_e$ ($τ_μ$) is a tau lepton that has an electron (muon) in the final state. In the present graduate thesis, we search for signatures of the production of a $Z'$ boson within the SSM framework in the final state channel $Z'→ τ_hτ_μ$. We analyze proton-proton collisions at a center of mass energy of $\sqrt{s}=13$ TeV, corresponding to data collected by the CMS experiment during the full LHC-Run 2. The hypothetical experimental signature of a $Z'$ can be obtained, through its tau lepton decays, on events with oppositely charged and almost back-to-back tau pairs with high transverse momentum. Missing transverse energy (MET) is expected in the signal events since neutrinos are produced in the tau decay chain, therefore, we look for a broad enhancement in the reconstructed mass distribution from MET, the tau, and muon leptons. We have performed optimization studies in the topological kinematical selections to maximize the signal significance over backgrounds. We have proposed control regions with orthogonal requirements to the signal region, to verify the MC simulation for backgrounds, and in the case of QCD we have implemented data-driven methods. After unblinding the signal region, no excess above the SM backgrounds has been observed as possible evidence of a $Z'$ boson, therefore, we have expanded the exclusion limits of the $Z'→ τ_hτ_μ$ channel up to masses of 3150 GeV.